Tras las huellas de la investigación en educación de la física desde los proyectos del IDEP, el CIUP y la Universidad Distrital Francisco José de Caldas en la década 1995–2005 - Reyes R., Jaime D. (Revista Científica, 2011)
This article presents an organization of the researches developed in the 1995-2005 decade about teaching and learning physics in Bogota. The categories used in this work arise as a result of the systematization of documentary information and take part of the development of doctoral thesis titled pedagogical content knowledge of pre-service physics teacher about teaching electric field. The papers used here were reported by the Instituto para la Investigación Educativa y el Desarrollo Pedagógico IDEP, the Centro de Investigaciones de la Universidad Pedagógica Nacional CIUP and the Universidad Distrital FJC, in the field of teaching and learning of physics. The documentation was analyzed from the database that the author and a research team previously built in the research project supported by the Centro de Investigación y Desarrollo Científico CIDC (Reyes, J., 2007).